English Teachers' Personality Competence in Utilizing ICT Technological Industry 4.0 at PKBM KREASI in Gunungsitoli Barat - Dwi Astuti Zebua; Maru’ao, Nursayani; Harefa, Afore Tahir; Daeli, Hidayati (Edu-Ling: Journal of English Education and Linguistics, 2024)
Personality competence is one of the teacher competencies that is very important in the success of the teaching and learning process. The purpose of this study is to determine the personality competence of teachers in utilizing industry 4.0 technology in the learning process. The method used in this research was qualitative analysis. The instruments used are observations, interview and questionnaire.  After analyzing the teacher's personality competence through observation and interview, the researcher found that the four English teachers had personality competence indicators, namely, presenting themselves as a person who has a good personality stable, mature, wise, and authoritative, showing work ethic, high responsibility, a sense of pride in being a teacher, and self-confidence and upholding the ethical code of the teaching profession. Both English teachers who have been observed use technology when teaching in the classroom. Although English teachers have obstacles in using technology, they are able to deal with them. Key Words: Qualitative Analysis, English Teachers, Personality Competence